Improvement of olfactory function for quality of life recovery. (17th May 2013) - Katotomichelakis, Michael; Simopoulos, Efthimios; Tripsianis, Gregory; Prokopakis, Emmanuel; Danielides, Gerasimos; Velegrakis, Stelios George; Livaditis, Miltos; Danielides, Vassilios
Abstract : Objectives/Hypothesis: To explore quality of life (QoL) improvement after treatment of patients with chronic olfactory disorders; and to correlate QoL with olfactory rehabilitation and evaluate olfactory improvement values over which QoL outcomes are significantly recovered. Study Design: Prospective clinical study. Methods: Eighty‐nine patients following endoscopic sinus surgery for chronic rhinosinusitis (CRS) and immunotherapy for allergic rhinitis (AR) were studied. Olfactory function was evaluated using Sniffin' Sticks test pre‐and 12 months after treatment. All patients completed six validated QoL questionnaires either specific for olfaction (Questionnaire of Olfactory Deficits‐QOD) and for assessing mental health (Zung Anxiety Scale, State‐Trait Anxiety Inventory, Zung Depression Scale, Beck Depression Inventory), or generic one (Short Form‐36). Results: Significant improvement (all P < 0.001) of olfactory function by 27.4% in total cohort (AR: 10.4%, P = 0.004; CRS: 39.9%, P < 0.001), expressed by the combined Threshold‐Discrimination‐Identification (TDI) score‐and of all QoL questionnaires scores (all P < 0.01) as well, was observed after treatment. There was a positive correlation between olfactory recovery and improvement of patients' QoL. ROC analysis revealed that an increase in the TDI score by 3.50 points in AR and 4.75 points in CRS was necessary for a clinically significant improvement in all QoL questionnaires results. Conclusions: QoL and mental health of patients suffering from chronic sinonasal diseases are totally recovered after treatment, presenting a direct positive relationship with smell improvement. An increase of olfactory function by 3.50 points for AR and 4.75 points for CRS might be considered the cutoff point for patients' QoL significant recovery. Level of Evidence: 4. Laryngoscope, 123:E10–E16, 2013